1995
DOI: 10.1007/bf02367779
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of microcirculation of the basal region of rat gastric mucosa

Abstract: We modified and improved techniques for the intravital microscopic observation of the rat gastric microcirculation. The stomach of anesthetized rats was cut along the greater curvature, and the posterior wall of the glandular stomach was fixed in a chamber with the serosal side up and perfused with warmed Tyrode's solution. A portion of the muscularis externa was resected with the serosa to make an observation window. Vascular casts were studied histologically after the injection of Monastral blue B gelatin so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…Igawa et al 8 also reported that the percentage of mucosal capillaries containing erythrocytes signifi cantly decreased after topical application of epinephrine. In these respects, topical application of epinephrine on the papilla may reduce papillary edema by decreasing capillary permeability or by relaxing the sphincter of Oddi, 7,8 and may be an inexpensive alternative for prevention of post-ERCP pancreatitis. To minimize post-ERCP pancreatitis, epinephrine sprayed on the papilla has been recommended anecdotally in Japan.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Igawa et al 8 also reported that the percentage of mucosal capillaries containing erythrocytes signifi cantly decreased after topical application of epinephrine. In these respects, topical application of epinephrine on the papilla may reduce papillary edema by decreasing capillary permeability or by relaxing the sphincter of Oddi, 7,8 and may be an inexpensive alternative for prevention of post-ERCP pancreatitis. To minimize post-ERCP pancreatitis, epinephrine sprayed on the papilla has been recommended anecdotally in Japan.…”
Section: Introductionmentioning
confidence: 98%
“…Ohno et al 7 reported that topical application of epinephrine constricted mucosal arterioles without affecting venules. Igawa et al 8 also reported that the percentage of mucosal capillaries containing erythrocytes signifi cantly decreased after topical application of epinephrine.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we were able to demonstrate directly that the gastric mucosa receives a prominent intrinsic innervation by ascending acetylcholine and, to a lesser extent, by descending nitric oxide synthesising myenteric neurones (Pfannkuche et al, 1998b;Reiche and Schemann, 1998). Both acetylcholine and nitric oxide influence acid, bicarbonate, pepsin, and mucus secretions (Fandriks, 1986;Raufman, 1992;Brown et al, 1993a,b;Bilski et al, 1994;Price et al, 1994;Hersey and Sachs, 1995), motility of the muscularis mucosae (Angel et al, 1983;Dobreva et al, 1994), and blood flow (Chen and Guth, 1995;Ohno et al, 1995). Cholinergic and nitrergic myenteric neurones in the guinea pig gastric corpus synthesise a number of other putative neurotransmitters and neuromodulators (Schultzberg et al, 1980;Mawe et al, 1989;.…”
mentioning
confidence: 95%
“…EC DAN is a transient process and appears as apoptotic debris sloughing off into the vascular lumen ( Figure 1A); therefore, it cannot be identified unless the tissues are collected proximate to the onset of damage. Also, definitive identification of EC damage may require electron microscopy (Ownby, Bjarnason, and Tu 1978;Sharma and Kiyatkin 2009), immunolabeling of apoptotic cells (Lim, DeLano, and Schmid-Schonbein 2001;Mikaelian et al 2010), quantification of ECs through immunolabeling (Copple et al 2002), or assessment of ethidium bromide uptake (Lim, DeLano, and Schmid-Schonbein 2001) or vascular leakage (Wiener and Giacomelli 1973;Joris et al 1982;Pino and Thouron 1983;Turek and Schoenlein 1993;Ohno et al 1995;Gyomber et al 1996;Joseph et al 1996a; Albassam et al Note: These findings are recorded and graded independently of the end points against which a biomarker is sought. FIGURE 1.-The main histomorphologic end points tracked by the lexicon of the VIWG of PSTC are degenerative and hyperplastic changes of ECs and VSMCs.…”
Section: Endothelium Degeneration/apoptosis/necrosismentioning
confidence: 99%